A new species of Calochortus (Liliaceae) from Oaxaca, Mexico - García-Mendoza, Abisaí; Sandoval Gutiérrez, Daniel; Chávez Rendón, César (Instituto de Ecología, A.C., 2023)
Background and Aims: The genus Calochortus is a monophyletic group endemic to North America. In Mexico, the Cyclobothra section is the richest and most widely distributed. During botanical explorations in the Mixtec region of Oaxaca, unknown Calochortus plants were collected, so the objective was to describe these as a new species for science.Methods: The taxon was compared with previously described species; herbarium collections and type specimens were reviewed. The morphological description, an illustration, and a distribution map were elaborated, and its relationships with nearby species were discussed. Its conservation state was evaluated according to the criteria of the NOM-059-SEMARNAT-2010 and the IUCN.Key results: Calochortus multicolor is described, which due to its morphology is situated in the section Cyclobothra subsection Barbati. It is compared to C. barbatus and C. marcellae, from which it differs by its ascending or erect and crateriform to campanulate flowers, green, greenish-yellow, brownish, rose colored or red; petals inside are densely covered with white or yellow hairs and a fimbriated membrane around the distal portion of the gland. The species is endemic to the Mixtec region, Oaxaca and according to the vulnerability criteria it is placed in the Threatened category (A) according to the Official Mexican Standard for Species at Risk and of Least Concern (LC), following the guidelines of the IUCN.Conclusions: Calochortus multicolor is recognized as a new entity for science, which grows on gypsum and calcareous soils, habitat of a large number of regional microendemic plants. It is considered necessary to develop strategies for the conservation of habitats and species in these areas of high floristic diversity.